Design of intervention for youth engagement in agripreneurship in Malawi - Chitika, R.; Nhlane, M.; Enokenwa Baa, Ojongetakah; Mokhema, Seipati; Davis, Kristin E. (International Water Management Institute (IWMI), 2024)
The CGIAR Initiative on Diversification in East and Southern Africa also known as Ukama Ustawi” (UU) Initiative’s goal is to empower millions of vulnerable smallholder farmers to transition from maize mixed systems to sustainably intensified, diversified, and de-risked agrifood systems is well underway. The initiative is being implemented in 13 African countries using coordinated transformative change interventions driven by an understanding of the unique multidimensional challenges and the opportunities they present in the different local and national contexts.